2007
DOI: 10.1177/1469044607083604
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ATP bioluminescence swabbing as a monitoring and training tool for effective hospital cleaning

Abstract: Effective cleaning in hospitals is an important aspect of infection control of pathogens such as methicillin resistant Staphylococcus aureus (MRSA). There is a need for simple, rapid methods of assessing cleanliness in order to effectively audit cleaning programmes and to educate staff. The aim of this study was to evaluate the use of adenosine triphosphate (ATP) bioluminescence swabs for assessing cleanliness in hospitals. Sites (n=108) in three hospital wards, including floors, patient equipment and clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 11 publications
(19 reference statements)
2
47
1
1
Order By: Relevance
“…This poor correlation is typical of that previously reported for such environments (Willis et al, 2007).…”
Section: Correlations Of Atp With Microbial Concentrationmentioning
confidence: 44%
“…This poor correlation is typical of that previously reported for such environments (Willis et al, 2007).…”
Section: Correlations Of Atp With Microbial Concentrationmentioning
confidence: 44%
“…Some studies reported poor correlation between ATP level and ACC. 11,17 However, Boyce and Fekieta 18 showed a low but significant level of correlation between log10 values of ATP and ACC. Our results were in agreement with the Boyce study.…”
Section: Discussionmentioning
confidence: 91%
“…Tangible values and trends over time from bioluminescencebased ATP data have the advantage of immediate and potentially longer-term feedback for housekeeping staff (260). The use of ATP monitoring appears to have a pronounced effect on cleaners, especially when they receive educational programs at the same time (247).…”
Section: Atp Bioluminescence Systemsmentioning
confidence: 99%